Exposure to indoor allergens and association with allergy symptoms of employees in a work environment - Barbara Brunetto (Annali dell'Istituto Superiore di Sanità, 2009)
Exposure to indoor allergens is an important risk factor for sensitisation and respiratory allergy. The aim of this paper was to evaluate the levels of mite, cat and latex allergens in dust collected from an indoor workplace and to assess whether the exposure to these allergens was associated with the allergy symptoms reported by employees. Sixty dust samples were collected. Allergen concentrations were measured with antibody based ELISAs. All 144 participants compiled a questionnaire exploring possible symptoms of allergy. No association between latex allergen exposure and symptoms was found in spite of the high frequency of latex allergens. Mite allergens were detected in a minority of rooms. Cat allergen was the most important indoor allergen in the sampled workplace and exposure to this allergen could represent a risk for employees.